Reshaping US Navy Pacific Response in Mitigating Disaster Risk in South Pacific Island Nations: Adopting Community-Based Disaster Cycle Management. Issue 1 (23rd December 2013) - Reaves, Erik J.; Termini, Michael; Burkle, Frederick M.
Abstract: The US Department of Defense continues to deploy military assets for disaster relief and humanitarian actions around the world. These missions, carried out through geographically located Combatant Commands, represent an evolving role the US military is taking in health diplomacy, designed to enhance disaster preparedness and response capability. Oceania is a unique case, with most island nations experiencing "acute-on-chronic" environmental stresses defined by acute disaster events on top of the consequences of climate change. In all Pacific Island nation-states and territories, the symptoms of this process are seen in both short- and long-term health concerns and a deteriorating public health infrastructure. These factors tend to build on each other. To date, the US military's response to Oceania primarily has been to provide short-term humanitarian projects as part of Pacific Command humanitarian civic assistance missions, such as the annual Pacific Partnership, without necessarily improving local capacity or leaving behind relevant risk-reduction strategies. This report describes the assessment and implications on public health of large-scale humanitarian missions conducted by the US Navy in Oceania. Future opportunities will require the Department of Defense and its Combatant Commands to show meaningful strategies to implement ongoing, long-term, humanitarian activities that will build sustainable, host nation health system capacity and partnerships. This report recommends a community-centric approach that would better assist island nations in reducing disaster risk throughout the traditional disaster management cycle and defines a potential and crucial role of Department of Defense's assets and resources to be a more meaningful partner in disaster risk reduction and community capacity building. EJ Reaves, M Termini, FM Burkle Jr. Reshaping US Navy Pacific response in mitigating disaster risk in South Pacific Island nations: adopting community-based disaster cycle management .Prehosp Disaster Med .2014 ;29 (1 ):1 -9 .